"What's inside Malay Forests?" Physical and spiritual narrative of the Malay forests in British-Malaya: (Ada apa dalam "Hutan Melayu"? Naratif fizikal dan spiritual hutan Melayu di zaman British-Malaya) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
According to the WWF, forests cover 30% of the earth's surface and act as important support systems in balancing the world ecosystem (World Wide Fund for Nature (WWF) n.d.). They are home to many plant and animal species and a critical source for sustaining human livelihood. Human dependency on forest products is the backbone of not only the survival of a nuclear family but also contributes to the economy of the local community. As known, Malaysian forests consist of mountainous forests, tropical rainforest, swamps and coastal forests. As for traditional Malay society, they relied heavily on forests for survival. Besides its functioning as a source of food, forests also contribute to the cultural aspects of society in the Malay civilisation. Hence, this study will analyse the image and description of the Malay forests based on the writing of British officers and writers during the colonial era such as Maxwell, Clifford, Swettenham, Fauconnier, Endicott, Winstedt, Skeat, Wilkinson and Annandale. By using a narrative approach and auto-ethnography, views of the Malay forest will be assessed from Western perspectives, which are based predominantly on the observations of British-Malaya colonial officers and Western scholars involved directly in the Malay community and their communal activities at the time. In summary, this writing will depict the worldview of the Malays about their forests, physically and spiritually, through the lens of Westerners.Keywords: Malay Forests, British-Malaya, British colonial, environmental history, Malay civilization